Physiological factors determining downhill vs uphill running endurance performance - Lemire, Marcel; Hureau, Thomas J.; Favret, Fabrice; Geny, Bernard; Kouassi, Blah Y.L.; Boukhari, Mourad; Lonsdorfer, Evelyne; Remetter, Romain; Dufour, Stéphane P. (Journal of science and medicine in sport, 2021)
Recent studies investigated the determinants of trail running performance (i.e., combining uphill (UR) and downhill running sections (DR)), while the possible specific physiological factors specifically determining UR vs DR performances (i.e., isolating UR and DR) remain presently unknown. This study aims to determine the cardiorespiratory responses to outdoor DR vs UR time-trial and explore the determinants of DR and UR performance in highly trained runners. Randomized controlled trial. Ten male highly-trained endurance athletes completed 5-km DR and UR time-trials (average grade: ±8%) and were tested for maximal oxygen uptake, lower limb extensor maximal strength, local muscle endurance, leg musculotendinous stiffness, vertical jump ability, explosivity/agility and sprint velocity. Predictors of DR and UR performance were investigated using correlation and commonality regression analyses. Running velocity was higher in DR vs UR time-trial (20.4±1.0 vs 12.0±0.5km·h−1, p<0.05) with similar average heart rate (95±2% vs 94±2% maximal heart rate; p>0.05) despite lower average V̇O2 (85±8% vs 89±7% V̇O2max; p<0.05). Velocity at V̇O2max (vV̇O2max) body mass index (BMI) and maximal extensor strength were significant predictors of UR performance (r2=0.94) whereas vV̇O2max, leg musculotendinous stiffness and maximal extensor strength were significant predictors of DR performance (r2=0.84). Five-km UR and DR running performances are both well explained by three independent predictors. If two predictors are shared between UR and DR performances (vV̇O2max and maximal strength), their relative contribution is different and, importantly, the third predictor appears very specific to the exercise modality (BMI for UR vs leg musculotendinous stiffness for DR).